Is there any such thing as a social or behavioural science? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Philosophy at Massey University - Russell, Michael Gordon (Massey University, 1985)
The type of explanation characteristic of science is causal, and it is natural to think that this type of explanation is appropriate for all events, no matter what their nature. It is this global assumption that is questioned in this thesis. Chapter One presents a historical exposition of the development of causal explanation since the time of David Hume. The perennial theme has been the conceptual separability of causally related events and the need to insert an empirical law to deduce one from the other. Karl Popper (the subject of Chapter Two) has also used this deductive feature of causal explanation, and even argues for the unity of science, social and natural, on the strength of it. Throughout this tradition social behaviour is supposedly caused and requires the same kind of explanatory apparatus as any other behaviour. The Wittgensteinian tradition (Chapter Three) opposes any such tradition by emphasizing the importance of normative rules governing human action, as opposed to any causal relations. In particular, the conceptual notion of a 'criterion of identity' is investigated in relation to both the natural and social sciences, and it is concluded that the logic of explanation works very differently in these two disciplines. This is so for two reasons. First, because the criteria of identity for any concept are logically, not contingently, related to that concept; and as the criteria for any action are the surrounding contexts, then those surrounding contexts cannot be the causes of the behaviour concerned in any Humean sense. Second, the criteria of identity are not imposed upon social phenomena from 'without', as is the case in the natural sciences; they are constituted from within, and thus a social science must base the rules it uses upon the criteria belonging to the group being studied rather than the group of researchers studying it. Social scientists cannot then give a causal explanation of human behaviour. But they can explain it by giving reasons; that is, by showing how the behaviour is conceptually related to the context by classifying it under the appropriate logical category. This point is emphasized in an investigation of the so-called 'Rationality Principle' in Chapter Four. Popper asserts that 'rational' behaviour is an 'appropriate' (causal) response to a particular problem situation; 'appropriate' being in accordance with the objective or brute facts. But the Wittgensteinian point remains however, i.e. that the problem which any agent is responding to is conceptually linked to that action and cannot therefore the cause of it. Furthermore, rationality cannot be measured against any Popperian 'objective' or 'brute' facts; rather, rational behaviour is so according to certain human conventions, and these conventions are normative rather than objective in the Popperian sense. Rational behaviour is not then behaviour in accordance with the 'facts', but behaviour in accordance with relative normative criteria of rationality. In conclusion, it is wholly inappropriate to explain human behaviour in terms of 'causes' and 'objective facts'.
Keywords: Human behavior -- Philosophy; Psychology